2016
DOI: 10.3389/fped.2016.00105
|View full text |Cite
|
Sign up to set email alerts
|

Association between Apnea of Prematurity and Respiratory Distress Syndrome in Late Preterm Infants: An Observational Study

Abstract: BackgroundLate preterm infants (34–36 weeks’ gestation) remain a population at risk for apnea of prematurity (AOP). As infants affected by respiratory distress syndrome (RDS) have immature lungs, they might also have immature control of breathing. Our hypothesis is that an association exists between RDS and AOP in late preterm infants.ObjectiveThe primary objective of this study was to assess the association between RDS and AOP in late preterm infants. The secondary objective was to evaluate if an association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
9
0
4
Order By: Relevance
“…4,10 Late-preterm infants have higher incidence of respiratory distress syndrome, transient tachypnea, apnea, and respiratory failure than term infants. [10][11][12] They have increased risk of developmental delays, often out of proportion for their level of illness in the hospital. 13 Significant cortical and cerebellar growth and maturation occur during the late-preterm period, indicating that even mild insults during this time frame could lead to significant consequences on later brain development.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Late-preterm infants have higher incidence of respiratory distress syndrome, transient tachypnea, apnea, and respiratory failure than term infants. [10][11][12] They have increased risk of developmental delays, often out of proportion for their level of illness in the hospital. 13 Significant cortical and cerebellar growth and maturation occur during the late-preterm period, indicating that even mild insults during this time frame could lead to significant consequences on later brain development.…”
Section: Discussionmentioning
confidence: 99%
“…В периоде новорожденности у таких младенцев могут развиваться нарушения, во многом обусловленные недостаточным вниманием к проблемам их вскармливания: гипотермия, гипогликемия, эксикоз, чрезмерная потеря массы и медленное ее нарастание, интенсивная желтуха [6,9,11]. Отмечены также высокий риск повторяющихся апноэ и повышенная восприимчивость к инфекциям [12,13].…”
Section: обоснованиеunclassified
“…For instance, various studies reported leading comorbidity as neonatal sepsis (26.1%–71%), hypothermia (63%), and apnea of prematurity (28.6%). 22 25 Beyond the impact of RDS on the neonate, the family and health system itself suffer repercussions. 26 …”
Section: Introductionmentioning
confidence: 99%